Folate-Functionalized CS/rGO/NiO Nanocomposites as a Multifunctional Drug Carrier with Anti-Microbial, Target-Specific, and Stimuli-Responsive Capacities - Obireddy SR; Ayyakannu A; Kasi G; Sridharan B; Lai WF; Viswanathan K (International Journal of Nanomedicine)
Sreekanth Reddy Obireddy,1,* Arumugam Ayyakannu,2,* Gopinath Kasi,3 Badrinathan Sridharan,4 Wing-Fu Lai,5 Karthika Viswanathan6,7 1Department of Urology, Zhejiang Provincial People’s Hospital, Affiliated People’s Hospital, Hangzhou Medical College, Zhejiang, 310014, People’s Republic of China; 2Department of Botany, Alagappa University, Karaikudi, Tamil Nadu, 630 003, India; 3School of Materials and Energy, Southwest University, Chongqing, 400715, People’s Republic of China; 4Department of Biomedical Engineering, Pukyong National University, Busan, 48513, Republic of Korea; 5School of Food Science and Nutrition, University of Leeds, Leeds, LS2 9JT, UK; 6Department Nanoscience and Technology, Alagappa University, Karaikudi, Tamil Nadu, 630 003, India; 7Department of Health Sciences, The Graduate School of Dong-A University, Busan, 49315, Republic of Korea*These authors contributed equally to this workCorrespondence: Wing-Fu Lai; Karthika Viswanathan, Email rori0610@graduate.hku.hk; karthikanano2021@gmail.comPurpose: This study reports the synthesis of surface-modified chitosan (CS) coated with reduced graphene oxide/nickel oxide (rGO/NiO) as a multifunctional drug carrier with anti-microbial, target-specific, and stimuli-responsive capacities. CS, rGO, and NiO nanoparticles are selected due to their pH-responsiveness, large surface area, and ROS generating-capacity, respectively.Methods: The CS/rGO/NiO nanocomposites (NCs) are synthesized using a solvothermal approach. Glutaraldehyde is used to crosslink CS and rGO/NiO to enhance the stability of the NCs. Structural properties, magnetic properties, antimicrobial activity, drug release sustainability and toxicity of the NCs are evaluated.Results: The NCs show good biocompatibility, excellent magnetic properties, good target specificity, and remarkable cell growth inhibitory effects. The release of doxorubicin (DOX) from the drug-loaded NCs at pH 5.0 (~98.6%) is much higher than that at pH 7.4 (~9.6%). Furthermore, the NCs inhibit the growth of A549 and MCF7 cells, causing the viability of A549 and MCF7 to drop to 12.3% and 7.1%, respectively. By using zebrafish embryos as a model, no detectable change is observed in the survival rate of the embryos after NC treatment.Conclusion: The NCs exhibit multifunctional, target-specific, and pH-responsive characteristics. These properties make the NCs a promising candidate for use in drug delivery applications.Keywords: nickel oxide, nanoparticles, biopolymer, folate receptor, drug delivery